Oxy-inflammation in hyperbaric oxygen therapy applications - Gerardo Bosco; Andrea Brizzolari; Matteo Paganini; Enrico Camporesi; Alessandra Vezzoli; Simona Mrakic-Sposta (European Journal of Translational Myology)
Hyperbaric oxygen therapy (HBOT) is a non-invasive method of O2 delivery that induces systemic hyperoxia. Hyperbaric chamber consists of a pressure vessel and a compressed breathing gas supply, which can regulate internal pressure. The chamber delivers 100% O2 to patients according to predetermined protocols and is monitored by trained personnel. HBOT relies on increasing the inspired O2 fraction (fiO2) and elevating the partial pressure of O2 (pO2). O2 is typically administered at pressures between 1.5 and 3.0 ATA for 60 to 120 minutes, depending on the clinical presentation. Currently, there are 15 indications for HBOT approved by the Undersea and Hyperbaric Medicine Society, categorized into three groups: emergency medicine, wound healing acceleration, and antimicrobial effects. The present narrative review aims to elucidate the mechanisms action underlying HBOT, particularly oxy-inflammation, in various pathologies within these categories.